Anassessment Of Central Information Commission (Cic) Duringpendemic (International Journal of Food and Nutritional Sciences, 2023)
In today's world information is the basic pre-requisite for safe and sound life. Having proper information helps to deal with everyday dynamics. In case of liberal democratic country like India, it is not wrong to say that information is directly related to empowerment. With this intent the Parliament passed the Right to Information Act on 15th June 2005 and it come into effect on 12th October 2005. Under Right to Information act information commissions are the final appellate authorities to decide on apples and complaint of citizens who have been denied their right to information under the law. Information Commission have been set up at the Central level i.e. Central Information Commission. This paper will examine the performance of information commission and implementation of this RTI act during Covid 19 pandemic and before. Finally the remarkable innovative step initiated by the state government and suggestion of some measure towards its effective use and execution.